Media at lipunan - 4 0 16; Tolentino, Roland B.,;Santos, Josefina M. C.; 5 University of the Philippines Press (Diliman, Quezon City : University of the Philippines Press, 2014)
Role of media in culture and society in the Philippines.
Includes bibliographical references (pages 381-388) and index.
In Tagalog.
Keywords: 2 -- 0; 6; Social aspects. -- Mass media -- Philippines -- 20; 20; 2